Francophone Cultures and Geographies of Identity. - Fagyal, Zsuzsanna (Cambridge Scholars Publishing, 2013)
This collection of original essays challenges French-centered conceptions of francophonie as the shaping force of the production and study of the French language, literature, culture, film, and art both inside and outside mainland France. The traditional view of francophone cultural productions as offshoots of their hexagonal avatar is replaced by a pluricentric conception that reads interrelated aspects of francophonie as products of specific contexts, conditions, and local ecologies that em ...